Membrane-Modified Metal Triazole Complexes for the Electrocatalytic Reduction of Oxygen and Carbon Dioxide - Supakul, Skye N.; Barile, Christopher J. (Frontiers in Chemistry, 2018)
In this manuscript, an electrochemical architecture is designed that controls the kinetics of proton transfer to metal triazole complexes for electrocatalytic O2 and CO2 reduction. Self-assembled monolayers of these catalysts are attached to a glassy carbon electrode and covered with a lipid monolayer containing proton carriers, which acts as a proton-permeable membrane. The O2 reduction voltammograms on carbon are similar to those obtained on membrane-modified Au electrodes, which through the control of proton transfer rates, can be used to improve the selectivity of O2 reduction. The improved voltage stability of the carbon platforms allows for the investigation of a CO2 reduction catalyst inside a membrane. By controlling proton transfer kinetics across the lipid membrane, it is found that the relative rates of H2, CO, and HCOOH production, can be modulated. It is envisioned that the use of these membrane-modified carbon electrodes will aid in understanding catalytic reactions involving the transfer of multiple protons and electrons.